Kant's concept of dignity - Schönrich, Gerhard; Kato, Yasushi, 1956- (Kantstudien. Ergänzungshefte., 2019)
This series publishes outstanding monographs and edited volumes that investigate all aspects of Kant's philosophy, including its systematic relationship to other philosophical approaches, both past and present. Studies that appear in the series are distinguished by their innovative nature and ability to close lacunae in the research. In this way, the series is a venue for the latest findings in scholarship on Kant